2015
DOI: 10.1016/j.ultsonch.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound assisted extraction of bioactive components from brown seaweed Ascophyllum nodosum using response surface methodology

Abstract: The objective of this study was to investigate the effect of key extraction parameters of extraction time (5-25 min), acid concentration (0-0.06 M HCl) and ultrasound amplitude (22.8-114 μm) on yields of bioactive compounds (total phenolics, fucose and uronic acid) from Ascophyllumnodosum. Response surface methodology was employed to optimize the extraction variables for bioactive compounds' yield. A second order polynomial model was fitted well to the extraction experimental data with (R(2)>0.79). Extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
108
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 29 publications
7
108
4
2
Order By: Relevance
“…Extraction of astaxanthin, novel carotenoid from green algae Haematococcus pluvial [94] Accelerate extraction of high molecular weight phenolic compounds from brown seaweed Ascophyllum nodosum [95] Highest kappa carrageenan yield (49.1%) with high purity comparable to standard reference was obtained from Hypnea musciformis using UAE [96] Supercritical fluid extraction (SFE)…”
Section: Microwave-assisted Extraction (Mae)mentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction of astaxanthin, novel carotenoid from green algae Haematococcus pluvial [94] Accelerate extraction of high molecular weight phenolic compounds from brown seaweed Ascophyllum nodosum [95] Highest kappa carrageenan yield (49.1%) with high purity comparable to standard reference was obtained from Hypnea musciformis using UAE [96] Supercritical fluid extraction (SFE)…”
Section: Microwave-assisted Extraction (Mae)mentioning
confidence: 99%
“…This environmentally benign and cost effective method has successfully extracted highly purified fibrils/nanofibrils from cellulosic materials [81,110]. Although UAE method has been utilized in extraction of bioactive compounds from several marine algae or even non-hydrocolloids materials [81,94,95,111,112]. Still, these were limited studies regarding extraction of seaweed hydrocolloids with this green method.…”
Section: Ultrasound-assisted Extraction (Uae)mentioning
confidence: 99%
See 1 more Smart Citation
“…The CPC has been widely applied in the food, pharmaceutical, and cosmetic industries due to their unique antioxidant and anti-inflammatory properties (Kuddus et al, 2013). The extraction of CPC from Spirulina platensis can be performed by various methods, such as solvent extraction by maceration and soxhlet methods, however, these conventional techniques are time-and solvent consuming (Kadam et al, 2015;Hadiyanto et al, 2015). Moreover, the extraction using conventional method does not give pure and high yields and it uses large amount of solvents which are detrimental to human as well as environment (Shirsath et al, 2012;Setyoningrum et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At higher temperature, phycocyanin structure will be destructed due to coagulation of phycobiliprotein (Sarada et al, 1999;Antelo et al, 2008). Besides temperature, the extraction time was also considered as important parameter for bioactive compound extraction (Kadam et al, 2015). Furthermore, Kadam et al,(2015) showed that increasing the extraction time could gained more extracted bioactive compound from plant material, and it could be shortened by using ultrasound assisted extraction (UAE) method.…”
Section: Introductionmentioning
confidence: 99%